The presumption of innocence in international human rights and criminal law - Coleman, Michelle (Lecturer in law) (London ; New York : Routledge, Taylor & Francis Group, 2021)
"This book examines the presumption of innocence from both a practical and theoretical point of view to determine what the presumption of innocence is and how it operates within law. The book approaches the right to presumption of innocence from an international human rights perspective using specific examples drawn from international criminal law. The result is a framework for understanding the right that is grounded in human rights law. This framework can then be applied across different national and international systems. When applied, it can help determine when the presumption of innocence is being infringed upon, eroded, violated, and enable the development of a remedy for the violation and ensuring that the presumption of innocence is protected"--
The presumption of innocence in context -- Who has the right and when does it become operable? -- Who carries the duty to uphold the presumption of innocence? -- The procedural aspect of the presumption of innocence -- The non-procedural aspect of the presumption of innocence -- The relationship between the presumption of innocence and pre-determination detention.
Includes bibliographical references and index.
Catalography
Description based on online resource; title from PDF title page (Site, viewed (04/23/21).
Keywords: Presumption of innocence; International law and human rights; International criminal law